Experiência e reflexão sobre a educação do campo na comunidade Nossa Senhora da Conceição em Anapu-PA - SOUSA, Andreia Leão de (2023)
This article aims to reflect on the Education of the Field in the Community of Our Lady of Conception, which is located in the vicinal Surubim Munícipio de Anapu PA. Taking into account the experiences of the families of this locality, I show a little what they faced to get schools, churches and other basic resources. In this work I will highlight the school Osvaldo cruz because it was in it that I did my internships, so I have the opportunity to know better some parents, teachers and students, as well as the subjects related to this school, such as the curriculum, the Political Pedagogical Project (PPP), the work of organizing teachers and their professional situation.In addition, because I am doing the course of Field Education with emphasis on Languages and codes, I bring some information from this area of study.